Um novo olhar para a leitura de romances pelos alunos do 6 ano do ensino fundamental em uma escola pública de Patos de Minas - MG - BORGES, Janderson da Silva (2020)
This work is characterized as an action research whose main aspects are to benefit participants through innovative educational processes in order to transform educational methodologies thus making students more participative and interacting better with teaching-learning processes. The research aimed to find strategies to improve the process of reading novels by students of the 6th grade of Elementary School II and the production of comics books (HQ) in digital environment, through the retextualization proposed by Dell'Isola (2007). We also use as theoretical reference Bakhtin (2010), Iser (1996), Chartier (1998), Colomer (2007), Marcuschi (2008) among others. For the reading of Maurice Druon’s The Boy of the Green Finger, we carry out various activities such as reading workshops in the square, literary picnic, literary diary, painting on canvas, planting seedlings and creating comics as a way to encourage reading and the production of students' texts. We emphasize that interdisciplinary with the disciplines Science and Mathematics collaborated so that the workshops held could have the expected success. Workshops in external environments, leaving the common spaces of the school, were the ones that the students showed a greater interest in literary reading and the realization of textual production activities, from the retextualization in virtual environment. Finally, we find that placing students as protagonists of activities with teacher mediation is a way to promote the formation of literary readers in the final years of basic education so that they can become autonomous readers. In addition to proposing activities involving other disciplines showed that the expected results for students in the final years of elementary school, is not exclusive to Portuguese language teachers, because the other subjects also work with readings.